SPECTRAL ANALYSIS OF HEART RATE VARIABILITY IN PATIENTS WITH CORONARY ARTERY DISEASE - Mubarak, Sadia; Imran Majeed, Syed Muhammad; Khan, Muhammad Alamgir (Pakistan Armed Forces Medical Journal, 2023)
Objective: To carryout frequency domain analysis ofheart rate variability in patients with coronary artery disease. Methods: Forty coronary artery disease patients with coronary artery stenosis greater than 70% of at least one vessel lumen were included. Patients with diabetes mellitus, atrial fibrillation, structural heart diseases and bundle branch block were excluded. DMS 300 4A Holter monitors were used to obtain long-term 12 lead digital ECG recordings. Cardio Scan premium luxury software was used for analysis of heart rate variability. Results: The mean values of heart rate variability in patients were TP (2171.70 ± 1028.7), VLF (1661.41 ± 807.88), LF (392.71 ± 227.92), HF (112.03 ± 77.90) and LF/HF ratio (4.03 ± 1.75). On comparison with normal reference values there was a significant decrease (p-value < 0.05) in all parameters except VLF (p-value = 0.351). TP was reduced in all the patients (100%), VLF in 26 (65%), LF in 36 (90%), HF in 36 (90%) and LF/HF ratio in 29 (72.5%) patients. The difference between the frequency of patients with decreased heart rate variability was statistically significant (p-value < 0.05) except VLF (p-value = 0.082). Conclusion: Heart rate variability decreases significantly in patients with coronary artery disease.